Influência do fenômeno veranico na produtividade da soja na mesorregião do Triângulo Mineiro/Alto Paranaíba - MG - Roldão, Aline de Freitas (2015)
In the regions of tropics most of the agricultural activities depends directly on the rainy season, especially annual crops that are planted and harvested in the rainy season, as is the case of soybeans. Even the weather being an influencer agent in agricultural practices, cultivated plants are increasingly resistant to its anomalous phenomena, such as dry periods within the rainy season designated as dry spells. It occurs because of the large insertion of technologies employed in agriculture. This study analyzes the relationship between the occurrence of dry spells and soybean yield in the middle region of Triangulo Mineiro / Alto Parnaíba - MG in order to update the understanding of the degree of dependence of this important crop in relation to rainfall variability within the rainy season. The mesoregion of Triângulo Mineiro / Alto Paranaíba is located in the western portion of the state of Minas Gerais and has a population of 2,144,482 inhabitants and an area of 90,540 km². It is the largest producer of soybeans in Minas Gerais, responsible for 56.8% of the total production in the state. For the production of this research, it were used the historical time series of 30 rainfall stations of ANA, covering the period of 1980-2013 (34 years). The soybean productivity data were acquired by the IBGE (SIDRA), encompassing the period from 1990 to 2012 (23 years). Water balances were calculated by Thornthwaite and Mather methodology (1955). These were needed for the counting of dry spells and also for the delimitation of the rainy season. From the soybean productivity data with the respective total dry spells occurrences were prepared scatter plots and calculated Pearson\'s correlation coefficient between the two variables. As the delimitation of the rainy season, was obtained as the average beginning in the mesoregion on October 19 and ending on April 11, with an average duration of 175 days. 3553 dry spells occurred during the study period, being 77% of them (2745 events) of duration between 5 and 9 days. The month of February was the one that amounted more occurrences, 1326, corresponding to 37% of the total found in the mesoregion. Next was the month of December with 1173 records, 33% of the total and finally the month of January, which scored 1054 occurrences, an amount equivalent to 30% of the total. In respect to correlations between the total dry spells and soybean productivity, among the 30 locations, 21 had negative correlations, proving the fact that the higher the total dry spells is, lower soybean productivity is too. Most had a moderate correlation, i.e. 10 rainfall stations, equivalent to 33% of the total analyzed, the correlation obtained medium results. The 9 remaining locations presented positive and weak correlations, indicating that there is no relationship between the variables analyzed.